(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This article explores the role of realia—authentic cultural objects and materials—in fostering intercultural competence (IC) among foreign language learners. The study highlights how realia, by providing tangible cultural experiences, enhance learners’ ability to understand, respect, and effectively communicate across different cultures. Employing qualitative research methods, including teacher interviews and classroom observations, the study examines practical applications and challenges of using realia in language teaching. Findings suggest that realia significantly increase learner engagement, cultural empathy, and contribute to deeper intercultural understanding.